Boosting Creativity, but Only for Low Creative Connectivity: The Moderating Effect of Priming Stereotypically Inconsistent Information on Creativity - Wen, Fangfang; Zuo, Bin; Xie, Zhijie; Gao, Jia (Frontiers in Psychology, 2019)
Previous researchers have documented that priming inconsistent stereotypic information boosts creativity. The current study further examined the moderating role of creativity connectivity—which is the degree to which people perceive a social group or professional role to be relevant to creativity—in the priming of information related to the boosting effects of creativity. Study 1 adopted a 2 (stereotypically inconsistent target gender: male vs. female) × 2 (priming types: stereotypically consistent information priming vs. stereotypically inconsistent information priming) group design in which 89 college students from Wuhan were enrolled to complete a priming paradigm and a poster-advertising-design task. As a result, we found that the activation of inconsistent stereotypic information boosted creativity compared with that of consistent stereotypic information, which replicated previous findings. Study 2 also adopted a 2 (creativity-domain connectivity: high vs. low) × 2 (priming types: stereotypically consistent information priming vs. stereotypically inconsistent information priming) group design in which 85 college students from Wuhan were enrolled to complete the same tasks as in Study 1. The results of Study 2 indicated that when information with low relevance to creativity such as “a nurse” was primed, creativity was then significantly boosted by inconsistent stereotypic information such as “a male nurse” compared with the stereotypic one such as “a female nurse”. Conversely, when information with high relevance to creativity such as “a poet” was primed, there was no significant creativity-boosting effects between inconsistent stereotypic information such as “a dull poet” and the consistent one such as “an eccentric poet”. In sum, this study (i) replicated the previous findings in Chinese culture, and (ii) further explored the moderating role of creativity connectivity of the inconsistent stereotypic information.